2019
DOI: 10.1080/23808993.2019.1617632
|View full text |Cite
|
Sign up to set email alerts
|

Use of big data in drug development for precision medicine: an update

Abstract: Introduction: Big-data-driven drug development resources and methodologies have been evolving with ever-expanding data from large-scale biological experiments, clinical trials, and medical records from participants in data collection initiatives. The enrichment of biological-and clinical-context-specific large-scale data has enabled computational inference more relevant to real-world biomedical research, particularly identification of therapeutic targets and drugs for specific diseases and clinical scenarios. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 119 publications
0
50
0
2
Order By: Relevance
“…In 2016, laboratories were still physically mailing or faxing genomic reports in PDFs, which is a format that is extremely difficult for machines to read and interpret [12]. This clinical hurdle aside, in biomedical research this genomic inclusion in EHRs shows potential in secondary use as raw data from which to draw medically meaningful results [2,12,13]. Assuming that the EMR has adequate phenomic and genomic data on an individual, algorithms can translate raw data in EMRs to phenotype data, which in turn can be associated with the genomic data.…”
Section: Emrs and Phenotype-genotype Association Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2016, laboratories were still physically mailing or faxing genomic reports in PDFs, which is a format that is extremely difficult for machines to read and interpret [12]. This clinical hurdle aside, in biomedical research this genomic inclusion in EHRs shows potential in secondary use as raw data from which to draw medically meaningful results [2,12,13]. Assuming that the EMR has adequate phenomic and genomic data on an individual, algorithms can translate raw data in EMRs to phenotype data, which in turn can be associated with the genomic data.…”
Section: Emrs and Phenotype-genotype Association Researchmentioning
confidence: 99%
“…Successful examples have shown that EMR mining for potential recruitment are more cost efficient and less time consuming than traditional methods [35,36]. As a quantitative example, a study done in the US studied 31 EHR-driven analysis on drug-to-genome interactions and concluded that EHRs helped decrease the trial cost by 72% per subject and reduced the duration of the studies [13].…”
Section: Emr Use In Clinical Trialsmentioning
confidence: 99%
“…The beauty of in silico trials is that they are able to evaluate positive effects and drug toxicity precluding animal testing and reducing cost and time. 8 VPH models can incorporate numerous patient-specific variables, such as lifestyle, medical history, physical examination, diagnostic tests and genetics to make reliable predictions. 2 VPH might be used to predict the risk of developing certain conditions and determine which treatment should be used and when it should be started to prevent diseases on an individual level.…”
Section: Future Of Computational Modellingmentioning
confidence: 99%
“…A landmark study has highlighted the value of genetic evidence linking a target and disease for drug discovery (3), estimating that selecting targets supported by genetic data could double the success rate in the clinical development pipeline. Experts routinely consult large biomedical and genomic data resources (4) to guide target identification and validation. Examples for the field of oncology include The Cancer Genome Atlas (TCGA) (5) or the Cancer Dependency Map (DepMap) (6).…”
Section: Introductionmentioning
confidence: 99%